In the name of God : the Bible in the colonial discourse of empire - Crouch, Carly L. (Carly Lorraine), 1982-; Stökl, Jonathan, 1977- (Brill, 2013)
In In the Name of God biblical scholars and historians begin the exciting work of deconstructing British and Spanish imperial usage of the Bible as well as the use of the Bible to counteract imperialism.